Pengaruh Budaya Organisasi, Motivasi dan Lingkungan Kerja terhadap Kepuasan Kerja: (Studi pada Karyawan X Group Divisi Maintenance & Project Jakarta) - Delia Annisya Chairunas; Syaiful Anwar (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to investigate the influence of organizational culture, work motivation, and work environment on job satisfaction at X Group. The research focuses on understanding how these factors contribute to employees' overall satisfaction with their work. The sampling technique employed is Non-Probability Sampling, using the accidental sampling method, which selects respondents based on their availability and willingness to participate. The study’s sample consists of 30 respondents from a total population of 40 employees. Data analysis was performed using multiple regression analysis, with SPSS version 22 and Microsoft Excel 2019 as the software tools. The results of the study indicate that Organizational Culture (X1) has a non-significant effect on job satisfaction, meaning that the organizational culture at X Group does not substantially influence employees' job satisfaction. On the other hand, Work Motivation (X2) was found to have a significant effect on job satisfaction, suggesting that higher levels of motivation in the workplace lead to greater job satisfaction. Additionally, the Work Environment (X3) also showed a non-significant effect on job satisfaction, indicating that environmental factors within the company have a minimal impact on employees' overall satisfaction. The findings suggest that while organizational culture and work environment may play a role in job satisfaction, work motivation is the most influential factor. These results can help guide strategies to improve employee job satisfaction at X Group.